Innovation in small family businesses - Laforet, Sylvie (Cheltenham Edward Elgar Publishing Ltd., 2012)
"​Innovation in Small Family Businesses explores how innovation is developed and carried out in small family-owned businesses, the factors underpinning it, and the innovation drivers and barriers in these firms’ context. Sylvie Laforet also offers suggestions on how innovation can be fostered and perhaps, sustained in small family-owned businesses and discusses the government’s role in this. The book makes an important contribution to the theoretical development of family firms’ and small businesses’ innovation". (from the publisher)
1. Introduction -- 2. Culture, structure, leadership, business goal, orientation and innovation -- 3. Characteristics and factors affecting innovation in family firms -- 4. Process of innovation in small family businesses -- 5. Conclusion
Includes bibliographical references and index.
Keywords: Enterprises; SMALL ENTERPRISES; FAMILY CORPORATIONS; BUSINESS MANAGEMENT; TECHNOLOGICAL INNOVATIONS; INNOVATIONS